The Effect of Different Obturation Techniques on the Sealing Ability of Root Canal Filling Materials - Regula Sri Lakshmi; Bhaskar Das; Apurva Jadhav; Harsha Haridas; Sabari Murugesan; Savadamoorthi Kamatchi Subramani (Journal of Pharmacy and Bioallied Sciences)
Background: The performance of root canal filling materials in sealing is crucial for the effectiveness of endodontic procedures as it prevents the escape of microorganisms and guarantees the durability of the treatment. Materials and Methods: The present in vitro investigation included the preparation of 90 human single-rooted teeth using a standardized process. These teeth were then randomly separated into three groups (n = 30) according to the obturation technique: Group A (Lateral Compaction), Group B (Thermafil), and Group C (Continuous Wave of Condensation). Furthermore, each group was separated into two subgroups based on the specific kind of root canal filling material employed: Subgroup 1 (Gutta-Percha) and Subgroup 2 (Resilon). The sealing capacity was evaluated using a dye penetration technique, with measurements conducted at three specific time intervals: 24 hours, 1 week, and 4 weeks after the obturation process. Statistical analysis of the data was conducted using analysis of variance and post hoc tests to identify significant differences across groups. Results: The findings showed that the Continuous Wave of Condensation method (Group C) had the lowest dye penetration, with an average depth of penetration of 1.2 mm. The Thermafil technique (Group B) followed closely with a penetration depth of 1.8 mm, while the Lateral Compaction technique (Group A) achieved a penetration depth of 2.5 mm. In terms of sealing ability, Gutta-Percha demonstrated superior performance compared to Resilon, achieving average penetration depths of 1.5 mm and 2.0 mm, respectively. Statistical analysis showed statistically significant differences between the groups (P < 0.05), with the Continuous Wave of Condensation approach utilizing Gutta-Percha showing the highest level of sealing effectiveness. Conclusion: In conclusion, the Continuous Wave of Condensation approach showed a substantial improvement in the sealing efficacy of root canal fillings when compared to the Lateral Compaction and Thermafil procedures.